Effects of Endotoxin on Type 3 Inositol 1, 4, 5‐Trisphosphate Receptor in Human Cholangiocytes. Issue 2 (31st December 2018) - Franca, Andressa; Carlos Melo Lima Filho, Antonio; Guerra, Mateus T.; Weerachayaphorn, Jittima; Loiola dos Santos, Marcone; Njei, Basile; Robert, Marie; Xavier Lima, Cristiano; Vieira Teixeira Vidigal, Paula; Banales, Jesus M.; Ananthanarayanan, Meenakshisundaram; Leite, M. Fatima; et al.
Abstract : Clinical conditions that result in endotoxemia, such as sepsis and alcoholic hepatitis (AH), often are accompanied by cholestasis. Although hepatocellular changes in response to lipopolysaccharide (LPS) have been well characterized, less is known about whether and how cholangiocytes contribute to this form of cholestasis. We examined effects of endotoxin on expression and function of the type 3 inositol trisphosphate receptor (ITPR3), because this is the main intracellular Ca 2+ release channel in cholangiocytes, and loss of it impairs ductular bicarbonate secretion. Bile duct cells expressed the LPS receptor, Toll‐like receptor 4 (TLR4), which links to activation of nuclear factor‐κB (NF‐κB). Analysis of the human ITPR3 promoter revealed five putative response elements to NF‐κB, and promoter activity was inhibited by p65/p50. Nested 0.5‐ and 1.0‐kilobase (kb) deletion fragments of the ITPR3 promoter were inhibited by NF‐κB subunits. Chromatin immunoprecipitation (ChIP) assay showed that NF‐κB interacts with the ITPR3 promoter, with an associated increase in H3K9 methylation. LPS decreased ITPR3 mRNA and protein expression and also decreased sensitivity of bile duct cells to calcium agonist stimuli. This reduction was reversed by inhibition of TLR4. ITPR3 expression was decreased or absent in cholangiocytes from patients with cholestasis of sepsis and from those with severe AH. Conclusion: Stimulation of TLR4 by LPS activates NF‐κB to down‐regulate ITPR3 expression in human cholangiocytes. This may contribute to the cholestasis that can be observed in conditions such as sepsis or AH.